La resolutio come metodo della metafisica secondo Cornelio Fabro - Villagrasa, L.C., Jesús (Alpha Omega, 2018)
Summary: Cornelio Fabro claims that (Thomist) metaphysics follows the «resolutio» method. «Resolutio» is a notion that western rationalist tradition forgot, but which St. Thomas treated in an original manner. Nevertheless, Fabro's works do not include a systematic study on resolution nor an explicit treatment of the method of metaphysics. According to Heidegger and Fabro, the task of metaphysics is a reductio or resolutio of being (ens) to its foundation (esse). Without a study on method there seems to be no way of accomplishing this endeavour, and the passage from phenomenon to foundation. After some introductory considerations on method in general, the article gathers together Fabro's most significant remarks on «resolutio», pointing out the absence of any reference to the principal Thomist texts on the theme: In «Boethii de Trinitate» q 6, a 1, which presents the different types of «resolutio» in St Thomas. The article also considers the diverging interpretations given to this text by J. Aertsen and L. Oeing-Hanhoff. It concludes with a proposal on how to integrate into Fabro 's interpretation of St Thomas' philosophy an explicit study, and above all the use, of the resolutive method.